Faktor Mobilisasi Dini, Obesitas dan Usia Tua Sebagai Prediktor Lama Rawat Inap Pasien Fraktur Femur Pasca Bedah - Indra, Muhammad Fikri; Masfuri, Masfuri; Yona, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the factors that influence the length of stay in post-surgical femur fracture patients, specifically the interaction between early mobilization, obesity, and old age as potential predictors of hospitalization. The research method used was a systematic review using the PRISMA search strategy. The databases used in this research are ProQuest, Sage Journal, Embrace, Science Direct, and Scopus. The results of the study show that factors that influence the length of stay of postoperative femur fracture patients from the results of the literature review are mobility, comorbidities, related fractures, intraoperative blood loss, postoperative blood transfusion, occurrence of pressure ulcers, higher BMI or obesity, choice of anesthesia, and drainage status. The average length of stay in the literature review is 5.64 days to 14.4 days. In conclusion, many factors influence LOS such as mobility, comorbidities, related fractures, intraoperative blood loss, postoperative blood transfusion, and the occurrence of wounds. pressure, higher BMI or obesity, choice of anesthesia, drainage status. The average length of stay in research journals is 5.64 days to 14.4 days. Keywords: Fracture, Femur, Early Mobilization, Obesity, Old Age.